Mothers’ role expectations on their eldest young adult daughters: an exploratory study - Alcasid, Mary Angela Gwen R.; Napeñas, Jasmine Rose N.; Daloos, Ma. Lara Angela S. (Quezon City University of the Philippines Diliman, 2025)
This study seeks to explore mothers’ role expectations on their eldest young adult daughter (EYAD), the factors that influence their construction, and how they relate to existing social norms for women. Nine mothers were selected from purposive and snowball sampling and participated in a semi-structured interview, which discussed related narratives and experiences. The gathered data was coded and analyzed through identifying significant patterns and organizing salient themes. Results show that mothers have a diverse set of expectations of their EYADs related to various aspects of family life, such as the household and its members. These include emotional support and physical maintenance, promoting the welfare of the members, and achieving personal growth. These expectations mostly reinforced pre-existing social norms for women, but a few also deviated. As such, these roles were found to be influenced by several factors both within and outside the family. The results also highlight incidental findings that show the implications of other experiences within the family to the EYADs’ expected roles. The findings provide meaningful insights regarding family roles and division of labor, which promote a better understanding of social norms and the concept of equality within the family in order to build improved familial dynamics and inclusive societies.
In partial fulfillment for the Degree of Bachelor of Science in Family Life and Child Development
Thesis
Keywords: Mothers and daughters -- Philippines; Social norms; Role expectations